King Sigismund of Poland and Martin Luther: the reformation before confessionalization - Nowakowska, Natalia (Oxford University Press, 2018)
The Polish monarchy had a great impact on the rise of Lutheranism. King Sigismund (1506-1548) turned a blind eye to many Lutheran activities, and this study sees his tacit acceptance as an argument for the notion that he didn't see Lutheranism as a threat to the existing catholic Christianity, but as a variant form of the same faith.